Green-synthesized zinc oxide nanoparticles using Echinops spinosus extract: A promising anticancer agent for hepatocellular carcinoma - Hamad, Rabab S.; Elshaer, Mohammed Ahmed Ali; El-Mahdy, Hesham A.; Mohammed, Osama A.; Jeelani, Mohammed; Doghish, Ahmed S.; Abd-Elraheem, Mohamed Awad Mahmoud; Abdel mageed, Mervat Mostafa; Darwish, Amira Abd-elfattah; Ibrahim, Elwathiq Khalid; El-Dakroury, Walaa A. (PLOS ONE, 2025)
The environmentally sustainable synthesis of nanoparticles has arisen as a viable alternative to traditional methods, tackling ecological and economic issues. This research investigates the green synthesis of ZnO nanoparticles utilizing an aqueous extract of Echinops Spinosus L. roots (ESRE), abundant in bioactive chemicals, as a natural reducing agent. The impacts of different quantities of precursors and reducing agents were methodically examined. The synthesized ZnO nanoparticles were characterized by zeta potential measurements (−15.2 mV), transmission electron microscopy (TEM), which indicated spherical and hexagonal morphologies with an average size of 20.47–48.22 nm, and energy-dispersive X-ray spectroscopy (EDX), confirming zinc and oxygen as the principal elements. Fourier transform infrared spectroscopy (FTIR) underscored plant-derived compounds’ contribution to nanoparticle stabilization. Cytotoxicity was assessed using the MTT assay on two cancer cell lines, HepG2 (hepatocellular carcinoma) and MCF-7 (breast cancer). The green-synthesized ZnO nanoparticles had substantial anticancer efficacy, with the ZnO nanoparticles exhibiting the most pronounced anti-proliferative effect on HepG2 cells (10.4 folds) and 5.4 folds more effective in MCF-7 cells compared to ESRE, with HepG2 cells IC50 value of 19.94 ± 0.11 µg/mL while the IC50 for MCF-7 cells was 75.65 ± 0.16 µg/mL. The results indicate that ZnO-NPs produced by green technologies exhibit significant potential as anticancer agents, especially for hepatocellular carcinoma treatment.